2017
DOI: 10.1111/obr.12500
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and behavioural strategies for self‐directed weight loss: systematic review of qualitative studies

Abstract: SummaryAimWe conducted a systematic review of qualitative studies to examine the strategies people employ as part of self‐directed weight loss attempts, map these to an existing behaviour change taxonomy and explore attitudes and beliefs surrounding these strategies.MethodsSeven electronic databases were searched in December 2015 for qualitative studies in overweight and obese adults attempting to lose weight through behaviour change. We were interested in strategies used by participants in self‐directed effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 48 publications
3
25
2
Order By: Relevance
“…Although Hartmann‐Boyce et al. () describe reframing as a new strategy, the data were not analyzed in that report and it simply noted the phenomenon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Hartmann‐Boyce et al. () describe reframing as a new strategy, the data were not analyzed in that report and it simply noted the phenomenon.…”
Section: Methodsmentioning
confidence: 99%
“…Methods for searching, screening, and data extraction are described in brief below but have been published in Hartmann‐Boyce et al. () and Hartmann‐Boyce, Fletcher, Jebb, and Aveyard (). These searches were updated and this analysis includes only those studies found in the previous and updated search in which content on reframing was identified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants desired continual monitoring by a someone else, echoing evidence that soliciting assistance has been found to increase accountability, enhance motivational support and is acceptabile 21,25,28,39 . However, these reports may also be attributable to the memory of successful weight‐loss during WW when they were weighed at each meeting.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many participants were likely to be still aiming for weight‐loss rather than maintenance, and may have limited experience of lapses and relapse. Evidence suggests that implementation of strategies and challenges in weight management change over time 26‐28 . For example, in a recent study, Pedersen et al 27 explored whether self‐regulation of food intake differed between short and long‐term weight loss maintainers, finding key differences around planning, shopping/storing and preparing/cooking behaviours.…”
Section: Introductionmentioning
confidence: 99%